2020
DOI: 10.1101/2020.08.19.20177188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission dynamics of COVID-19 in household and community settings in the United Kingdom

Abstract: Background: Households appear to be the highest risk setting for transmission of COVID-19. Large household transmission studies were reported in the early stages of the pandemic in Asia with secondary attack rates ranging from 5-30% but few large scale household transmission studies have been conducted outside of Asia. Methods: A prospective case ascertained study design based on the World Health Organization FFX protocol was undertaken in the UK following the detection of the first case in late January 2020.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 30 publications
5
75
3
Order By: Relevance
“…In 5 studies, 20,36,39,48,49 individuals older than 60 years were most susceptible to SARS-CoV-2 infection. Contact age was not associated with susceptibility in 9 studies, 26,28,32,44,47,58,66,67,70 although these were typically less powered to detect a difference. Figure 3 summarizes 15 studies 22,26,29,37,39,42,44,45,47,49,55,59,60,63,65 The second most examined factor was sex of exposed contacts, which was not associated with susceptibility for most studies 20,22,26,32,36,39,44,45,[47][48][49]58,[65][66][67]70 except 3.…”
Section: Jama Network Open | Global Healthmentioning
confidence: 97%
“…In 5 studies, 20,36,39,48,49 individuals older than 60 years were most susceptible to SARS-CoV-2 infection. Contact age was not associated with susceptibility in 9 studies, 26,28,32,44,47,58,66,67,70 although these were typically less powered to detect a difference. Figure 3 summarizes 15 studies 22,26,29,37,39,42,44,45,47,49,55,59,60,63,65 The second most examined factor was sex of exposed contacts, which was not associated with susceptibility for most studies 20,22,26,32,36,39,44,45,[47][48][49]58,[65][66][67]70 except 3.…”
Section: Jama Network Open | Global Healthmentioning
confidence: 97%
“…Existing individual-level observational studies of household transmission typically included household contacts identified through contact tracing. [4][5][6][8][9][10] These studies have estimated secondary attack rates among household contacts to be five to ten times as high as in non-household settings. 4,6 Most of these studies were conducted in Asia, included smaller numbers of households, and/or did not compare to households where no secondary transmission occurred.…”
Section: Introductionmentioning
confidence: 99%
“…It is also now clear based on viral shedding data that children play an important role in transmission [33], and may even have a higher viral load in the respiratory tract than adults [37]. A household contact study found that COVID-19 attack rates in families were higher when the primary case was a child [40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed children under 5 years have a higher viral load in the respiratory tract than adults or older children [37][38][39]. Another study showed that COVID-19 attack rates in families were higher when the primary case was a child [40]. In the United States, 9.8% of all cases of COVID-19 were children [41].…”
Section: Methodsmentioning
confidence: 99%